Halophyte Nitraria billardieri CIPK25 promotes photosynthesis in Arabidopsis under salt stress - Lu, Lu; Wu, Xinru; Tang, Yao; Zhu, Liming; Hao, Zhaodong; Zhang, Jingbo; Li, Xinle; Shi, Jisen; Chen, Jinhui; Cheng, Tielong (Frontiers in Plant Science, 2022)
The calcineurin B-like (CBL)-interacting protein kinases (CIPKs), a type of plant-specific genes in the calcium signaling pathway, function in response to adverse environments. However, few halophyte derived CIPKs have been studied for their role in plant physiological and developmental adaptation during abiotic stresses, which inhibits the potential application of these genes to improve environmental adaptability of glycophytes. In this study, we discovered that NbCIPK25 from Nitraria billardieri affects photosynthesis in such a way as to maintain seedling growth under salt condition. Our results show that Arabidopsis with NbCIPK25 expression exhibits more vigorous growth than wild type plants under salt condition. To gain insight into the molecular mechanisms underlying salt tolerance, we profiled the transcriptome of WT and transgenic plants via RNA-seq. GO and KEGG analyses revealed that upregulated genes in NbCIPK25 overexpression seedlings under salt stress are enriched in photosynthesis related terms; Calvin-cycle genes including glyceraldehyde-3-phosphate dehydrogenases (GAPDHs) are significantly upregulated in transgenic plants, which is consistent with a decreased level of NADPH (GAPDH substrate) and increased level of NADP+. Accordingly, NbCIPK25 overexpressing plants exhibited more efficient photosynthesis; soluble sugar and proteins, as photosynthesis products, showed a higher accumulation in transgenic plants. These results provide molecular insight into how NbCIPK25 promotes the expression of genes involved in photosynthesis, thereby maintaining plant growth under salt stress. Our finding supports the potential application of halophyte-derived NbCIPK25 in genetic modification for better salt adaptation.